Epineural Sleeve Reconstruction Technique for Median Nerve Complete Transection - Galanakos, Spyridon P. (Arch Bone Jt Surg, 2018)
In microsurgical nerve repair, the epineural sleeve technique can be used to bridge short nerve defects and to cover the coaptation site with the epineurium of the nerve stump. The epineurium serves as a mechanical aid to reduce gap size, and increase repair strength, effectively assisting nerve regeneration. This article presents a 32-year-old patient who experienced complete transection of the median nerve at the distal forearm, which was treated with the epineural sleeve graft reconstruction technique. Nerve regeneration was followed-up for 18 months and evaluated with the Rosén and Lundborg scoring system. The final outcome was excellent; at the last follow-up, the patient experienced complete sensory and motor function of the median nerve. Level of evidence: V